Escherichia coli challenge and one type of smectite alter intestinal barrier of pigs - Almeida, Juliana Abranches Soares (BioMed Central, 2013)
An experiment was conducted to determine how an E. coli challenge and dietary clays affect the intestinal barrier of pigs. Two groups of 32 pigs (initial BW: 6.9 ± 1.0 kg) were distributed in a 2 × 4 factorial arrangement of a randomized complete block design (2 challenge treatments: sham or E. coli, and 4 dietary treatments: control, 0.3% smectite A, 0.3% smectite B and 0.3% zeolite), with 8 replicates total. Diarrhea score, growth performance, goblet cell size and number, bacterial translocation from intestinal lumen to lymph nodes, intestinal morphology, and relative amounts of sulfo and sialo mucins were measured. The E. coli challenge reduced performance, increased goblet cell size and number in the ileum, increased bacterial translocation from the intestinal lumen to the lymph nodes, and increased ileal crypt depth. One of the clays (smectite A) tended to increase goblet cell size in ileum, which may indicate enhanced protection. In conclusion, E. coli infection degrades intestinal barrier integrity but smectite A may enhance it.